Ultrasound characteristics of normal parathyroid glands and analysis of the factors affecting their display - Wu, Cuiping; Zhu, Binyang; Kang, Song; Wang, Shiyu; Liu, Yingying; Mei, Xue; Zhang, He; Jiang, Shuangquan (BMC medical imaging, 2024)
Background Parathyroid glands are important endocrine glands, and the identification of normal parathyroid glands is crucial for their protection. The aim of this study is to explore the sonographic characteristics of normal parathyroid glands and analyze the factors affecting their display. Methods Seven hundred three subjects who underwent physical examination at our hospital were included. The number, location, size, morphology, echogenicity and blood flow distribution of parathyroid glands were recorded. The ultrasound characteristics and display rate were also summarized. Meanwhile, shear wave elastography was performed in 50 cases to provide the stiffness measurements, and 26 cases received contrast-enhanced ultrasonography for the assessment of microcirculatory perfusion. Furthermore, we analyzed the factors affecting parathyroid display, including basic information of the subjects and ultrasound features of the thyroid. Results ① A total of 1038 parathyroid glands were detected, among which, 79.29% were hyperechoic, 20.71% were isoechoic, 88.15% were oval-shaped, and 86.71% had blood flow of grade 0-I. ② 81.79% of the subjects had at least one parathyroid gland detected. ③ The Emean, Emax, PI and AUC of the parathyroid glands were significantly lower than those of the adjacent thyroid tissue ( P < 0.05). ④ The display of normal parathyroid glands was related to BMI, thyroid echogenicity and thyroid volume of the subjects ( P < 0.05). Conclusions Normal parathyroid glands tend to appear as oval-shaped hyperechoic nodules with blood flow of grade 0-I. BMI, thyroid echogenicity and thyroid volume are independent factors affecting the display of parathyroid glands.